Reactive oxygen species-mediated degradation of antidiabetic compounds: Cytotoxic implications of their photodegradation products - Challier, Cecilia (2018)
Reactive oxygen species (ROS) have been described in their double physiological function, helping in the maintenance of health as well as contributing to oxidative stress. Diabetes mellitus is a chronical disease nearly related to oxidative stress, whose treatment (in type II variant) consists in the administration of antidiabetic compounds (Andb) such as Gliclazide (Gli) and Glipizide (Glip). In this context, as Andb may be exposed to high ROS concentrations in diabetic patients, we have studied the potential ROS-mediated degradation of Gli and Glip through photosensitized processes, in the presence of Riboflavin (Rf) vitamin. We found that singlet oxygen (O 2 ( 1 ∆ g )) participated in the Rf-sensitized photodegradation of both Andb, and also superoxide radical anion in the case of Gli. Two principal products derived from O 2 ( 1 ∆ g )-mediated degradation of Gli were identified and their chemical structures characterized, through HPLC mass spectrometry. O 2 ( 1 ∆ g )-mediated degradation products and their toxicity was assayed on Vero cell line. These studies demonstrated that neither Gli nor its photoproducts caused cytotoxic effect under the experimental conditions assayed. Our results show strong evidences of ROS-mediated Andb degradation, which may involve the reduction or loss of their therapeutic action, as well as potential cytotoxicity derived from their oxidation products.